Branding Orientation in the Accommodation Industry - Liow, Melissa Li Sa; Chai, Yeow Kim (International Review of Management and Marketing, 2015)
This paper starts by clarifying the role of branding orientation (BO) among academic studies. It shortly introduces the development of the BO concepts. The empirical part consists of a search for and analysing of academic articles using a meta-analysis that consider BO in the accommodation industry. According to the results, significant appraisal of the branding building activities among higher star rating and luxury accommodation businesses are taking place due to the increasingly demanding guests. Thus, there is an upward pressure on small and medium accommodation businesses to survive or perform well. This paper recommends that scholars study the owners-managers, employees, and customer perspectives altogether, to better comprehend how large accommodation businesses displaying BO can generate superior performance. For the small and medium accommodation businesses, the emphasis is the owners-managers perceptions since they are the main decision-makers, and due to infancy of the small and medium enterprise (SME) branding application. Keywords: Branding Orientation; accommodation industry JEL Classifications: L83; M31